Elucidation of abrasive wear and slurry erosion behavior of Fe matrix composites reinforced with metallic coating modified ZTAP ceramics. Issue 8 (3rd August 2022) - Li, Cong; Shi, Jing; Li, Yuehui; Li, Yefei; Goei, Ronn; Gao, Yimin; Shah, Intizar; Zhao, Siyong; Tok, Alfred
ABSTRACT: Oxide ceramic particle-reinforced iron-based composites showed excellent abrasive wear resistance; however, the weak bonding property of the interfacial layer limited the application in harsh severe conditions. The combination of electroless plating (CVD) and multiarc ion plating technologies (PVD) was used to prepare Ni/Cr coatings on the surface of the ZTA ceramics, which effectively improves the interface bonding properties of the ZTAP /Fe composites. The interface of iron matrix composites reinforced by bare ZTA ceramic particles presented visible holes and crevices. After introducing Ni/Cr coating, a continuous and tight transition layer occurred at the interface between the ZTA ceramics and the Cr15 matrix. The diffusion and reaction of Ni and Cr nearby the interface caused a metallurgical bonding of composites. Abrasive wear and slurry erosion behavior of the ZTAP /Fe composites assisted with the metallic coatings was systematically investigated. The results indicated that the transition layer of the composites could effectively resist the removal and corrosion in the slurry fluids. Furthermore, the solid solution of Cr in the iron matrix improved the corrosion resistance of the Cr15 matrix in the artificial seawater medium. The ZTA ceramics and the Cr15 matrix were simultaneously cut under the SiC abrasive during two-body abrasive wear. ZTA ceramic particles play a protective role in the iron matrix due to their high hardness and excellent toughness. Graphical abstract: uf0001